New ages from Sehonghong rock shelter: Implications for the late Pleistocene occupation of highland Lesotho. (April 2017) - Pargeter, Justin; Loftus, Emma; Mitchell, Peter
Abstract: Sehonghong rock shelter is situated in the eastern Lesotho highlands, a climatically extreme region of southern Africa. The site is one of a handful in southern Africa that preserves human occupations before, during, and after the Last Glacial Maximum (LGM). The site's long and well-preserved sequence makes it relevant to addressing questions of human mobility, subsistence, and technology in relation to broader environmental change. Here we present a Bayesian-modelled radiocarbon chronology for the LGM and terminal Pleistocene occupations at Sehonghong. Our model incorporates previously published radiocarbon dates and new accelerator mass spectrometry ages. We also present archaeological evidence to test the hypothesis that Sehonghong was occupied in a series of punctuated events, and that some of these occupations were more intensive than others. Previous chronological and archaeological data were insufficient for testing these hypotheses. The new dates and archaeological data confirm that the site was occupied intensively in the early LGM and immediately thereafter. The site was otherwise occupied sporadically. We find that greater site occupation density is not always correlated with intensified use of local resources as measured by increased bipolar reduction and fish consumption. The new dates further confirm that Sehonghong contains some of the oldest evidence for systematic freshwater fishing in southern Africa. The availability of fish, a high fat protein source, probably stimulated human occupation, however sporadic, of such montane environments during cooler and drier periods. These findings suggest behavioural variability in response to shifting mobility and subsistence strategies. Our brief discussion informs upon hunter-gatherer occupation of southern African montane environments more broadly and human behavioural variability during the LGM.